تأثير طريقة المحاضرة والدافعية على زيادة اهتمام الطلاب مادة اللغة العربية في مدرسة المتوسطة الإسلامية الحكومية 4 بليتار - Choridah, Rifka Arifatul (Maharaat Lughawiyyat: Jurnal Pendidikan Bahasa Arab, 2024)
Learning interest is a crucial factor in determining the success of the learning process. However, in practice, many students show a lack of interest in certain subjects, such as Arabic. One of the causes is the use of less varied teaching methods and the lack of motivation instilled in students. This study aims to analyze the influence of lecture methods and motivation on increasing the learning interest of Grade VII students at MTsN 4 Blitar in Arabic subjects. This research uses a quantitative approach with multiple linear regression analysis. Data collection was carried out through questionnaires distributed to 51 students as the research sample. The analysis results show that the lecture method (X1) does not have a significant influence on increasing students' learning interest, with a significance value of 0.814 (> 0.05). On the other hand, motivation (X2) has a significant influence on increasing students' interest in learning, with a significance value of 0.008 (< 0.05). Simultaneously, the lecture method and motivation together have a significant influence on increasing student learning interest, as indicated by a significance value of 0.000 (< 0.05). This study concludes that motivation plays an essential role in stimulating students' interest in learning Arabic, while the lecture method requires support from other teaching strategies to be more effective.